Application of Project-Based Learning to Improve Communication Skills in Group B at Oasis Malang Kindergarten - Amitasari, Amitasari; Akbar, Mochammad Ramli; Anggraini, Henni (International Journal of Business, Law, and Education, 2025)
This study aims to describe the application of the Project-Based Learning (PjBL) model in improving the communication skills of Group B students at Oasis Kindergarten in Malang. The type of research used was Classroom Action Research (CAR) with a spiral model from Kemmis and McTaggart (Prihantoro & Hidayat, 2019), which included the stages of planning, action, observation, and reflection. The research subjects were 17 students in Group B in the second semester of the 2019/2020 academic year, consisting of 9 male students and 8 female students. This study was conducted in two cycles, focusing on improving children's communication skills, including listening, storytelling, and answering questions. The results showed that the application of the Project-Based Learning model could significantly improve children's communication skills. This improvement was evident from the evaluation results of communication skills, namely storytelling skills increased from 41.17% to 88.23%, answering questions skills from 35.29% to 82.35%, and asking questions skills from 23.52% to 82.35%. Based on these results, it can be concluded that the application of Project Based Learning is effective in creating active, collaborative, and meaningful learning that can develop the communication skills of early childhood at Oasis Kindergarten in Malang.